2013
DOI: 10.1128/jcm.02713-12
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative PCR for Detection of Shigella Improves Ascertainment of Shigella Burden in Children with Moderate-to-Severe Diarrhea in Low-Income Countries

Abstract: Estimates of the prevalence of Shigella spp. are limited by the suboptimal sensitivity of current diagnostic and surveillance methods. We used a quantitative PCR (qPCR) assay to detect Shigella in the stool samples of 3,533 children aged <59 months from the Gambia, Mali, Kenya, and Bangladesh, with or without moderate-to-severe diarrhea (MSD). We compared the results from conventional culture to those from qPCR for the Shigella ipaH gene. Using MSD as the reference standard, we determined the optimal cutpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
110
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 18 publications
7
110
0
1
Order By: Relevance
“…Hal ini menyatakan bahwa makin banyak jumlah koloni kuman Shigella, semakin banyak jumlah gen ipaH menyebabkan semakin berat derajat dehidrasi daripada diare. 16 Studi ini sesuai dengan hasil temuan kami mengenai jumlah koloni pada diare dengan dehidrasi ringan sedang dan berat lebih banyak daripada diare tanpa dehidrasi.…”
unclassified
“…Hal ini menyatakan bahwa makin banyak jumlah koloni kuman Shigella, semakin banyak jumlah gen ipaH menyebabkan semakin berat derajat dehidrasi daripada diare. 16 Studi ini sesuai dengan hasil temuan kami mengenai jumlah koloni pada diare dengan dehidrasi ringan sedang dan berat lebih banyak daripada diare tanpa dehidrasi.…”
unclassified
“…In addition to comparing detection rates, we aimed at evaluating the potential utility of pathogen loads, in terms of real-time PCR threshold cycle (C T ) values, to separate symptomatic from asymptomatic infections, as suggested by studies on norovirus, rotavirus, and Shigella infections (17)(18)(19).…”
mentioning
confidence: 99%
“…In a study conducted by Lindsay et al (2013), the authors observed that at 4.38 log 10 copies/mL of ipaH gene present in the stools of infants, a moderate to severe diarrheal infection occurred. Results in our study are substantially above this value; this may suggest that if Apies River water is consumed, this can lead to diarrhoeal infections in infants.…”
Section: Pathogen Concentrationsmentioning
confidence: 99%
“…Salmonellosis and shigellosis continue to be a major public health problem worldwide, with 93.8 million and 163.2 million cases, respectively, reported annually (Majowicz et al, 2010;Kotloff et al, 2013). Many interrelated factors contributing to this incidence include increased urbanization, inadequate supplies of clean water, antibiotic resistance and increased regional movement (Boehmer et al, 2009).…”
Section: Pathogen Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation